The Influence of E-Service Quality on Customer Engagement at Pangeran Beach Hotel - Figo Armando Sufli; Hendri Azwar (Pt. Threeple Herphi Educate, 2025)
Digital transformation in the hospitality industry has enhanced the role of Online Travel Agent (OTA) platforms in reservation processes and customer interactions. This study aims to examine the influence of e-service quality on customer engagement at Pangeran Beach Hotel Padang. E-service quality is measured across seven key dimensions: efficiency, fulfillment, reliability, privacy, responsiveness, compensation, and contact. Meanwhile, customer engagement is assessed through four indicators: learning, sharing, advocating, and socializing. Employing a quantitative causal-associative approach, data were collected through questionnaires distributed to 90 guests who made reservations via OTA. The data were analyzed using simple linear regression with SPSS version 31. The findings indicate that e-service quality has a positive and significant effect on customer engagement (R² = 0.308; p < 0.05), implying that the better the electronic service quality provided by the hotel, the higher the level of customer engagement. These results underscore the importance of improving digital services to enhance customer loyalty and foster sustainable interactions in the era of technology-driven hospitality.